Metasurface-based large field-of-view light receiver for enhanced LiDAR systems - Guo Hanwen; Zhou Xiangkun; Gao Bo; Yang Jianing; Zhang Lingyun; Wang Junya; You Zheng (Nanophotonics)
This paper presents a metasurface-based light receiver tailored for compact off-axis light detection and ranging (LiDAR) systems, addressing the critical challenge of simultaneously enhancing the field of view (FOV) and effective signal reception while adhering to strict size and weight limitations. A general design principle for the metasurface-based light receiver with large FOV capability is proposed, leveraging mapping relations to achieve optimal performance. As a proof of concept, a 20-mm-diameter 4-region metasurface device was designed and fabricated by deep ultraviolet (DUV) projection stepper lithography on an 8-inch fused silica wafer. The metasurface-based light receiver achieves a large FOV of ±30° and demonstrates a significant power enhancement ranging from 1.5 to 3 times at 940 nm when coupled with a 3-mm-diameter avalanche photodiode (APD). The innovation not only establishes a new paradigm for compact, high-performance LiDAR systems but also enables deployment in advanced fields such as unmanned aerial vehicles (UAVs) and miniaturized robots.